ASSESSMENT OF MANAGEMENT OF NEUROPATHIC PAIN PATIENTS IN A TERTIARY CARE HOSPITAL - SN, Akshay Kumar; DR, Bharathi; GR, Nataraj; Reddy, Brahmadi Shankar; Siddiq, Abubaker (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Neuropathic pain (NP) affects millions of people worldwide, and it is estimated that the prevalence among general population is 7–8 %. Chronic NP is more frequent in women compared to men and in patients above 50 years of age. Lower back, lower limbs, neck, upper lumbar and cervical painful radiculopathies are probably the most frequent sites of chronic NP. Objectives: To assess the neuropathic pain & prescription pattern, and management among NP patients. Materials and Methods: A prospective observational study was conducted in general orthopaedics department of Basaveshwara Medical College Hospital and Research Centre, Chitradurga. Results: In the present study 111 patients who were diagnosed with neuropathic pain were enrolled for the period AUG-2019 to MAR -2020. Females were found to be slightly more than males. The maximum predominant age group of both genders belongs to 40-59 years. 57.66% lumbar radiculopathy NP patients diagnosed were more than cervical radiculopathy 42.34%. Out of 236 total prescribed formulations for 111 patients, 17 active pharmaceutical ingredients with an average of 2 formulations per prescription were noticed. Prescription with combination therapy was common with more usage of pregabalin and mecobalamin followed by combinations of Non-Steroidal Anti-inflammatory and Antipyretic Drugs (NSAIDs) for the management of NP. NP patients preferred the usage of topical oil, balm applicants and hydro therapy along with regular treatment. Conclusion: The study concludes pregabalin and mecobalamin combination formulation is the most currently reliable medication in NP management and also defines additional therapy is the need along with the regular management of NP. Keywords: Neuropathic pain, Cervical radiculopathy, Lumbar radiculopathy, Non-Steroidal Anti-inflammatory and Antipyretic Drugs.